Effect of aromatic rings and substituent on the performance of lithium batteries with rylene imide cathodes - Aher, Jagdish; Graefenstein, Alexander; Deshmukh, Gunvant; Subramani, Kumar; Krueger, Bastian; Haensch, Mareike; Schwenzel, Julian; Krishnamoorthy, Kothandam; Wittstock, Gunther (ChemElectroChem, 2020)
Rylene imides (RIs) are attractive organic battery materials because of the inherent modularity of the molecules. While strong aggregation of RIs is disadvantageous for fast lithium-ion transport in the organic active material, decreasing the solubility of the RIs in battery electrolytes is essential to avoid performance fading. Therefore, the design and synthesis of RIs for lithium batteries is a non-trivial task that must, among other considerations, balance lithium-ion transport in the solid material vs. low solubility by controlling aggregation and packing. We have chosen triphenylamine (TPA) as a substituent which disrupts the aggregation but maintains a low solubility due to increased aromaticity of TPA. We have synthesized three RIs with one, two, and four aromatic units in the core. All of them showed stable specific capacity over 300 charge-discharge cycles. The batteries also showed specific capacities close to their theoretical capacities with 97-99 % coulombic efficiency. The maximum specific energy and specific power were 197 mWh g(-1) and 37 mW g(-1), respectively.
Keywords: lithium-ion batteries; organic cathode material; rylene imides; solubility; triphenylamine